Legal Protection Against Victims Tracked in Online Loans - Prasetya, Arie Zaky; Darwis, Darwis; Bahar, Randy; Situmeang, Rio Rozada (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The existence of technology has made it easier for people to carry out their activities, even now it has become part of their basic needs. Another convenience offered is borrowing funds. People who require funds, both in terms of meeting needs, business capital, or in a state of urgency, will take advantage of the existence of online loan applications. The conditions are even very easy as well as the disbursement process. This is what makes people tempted to use the application. However, it does not guarantee legal protection due to the absence of legal instruments in an agreement made by both parties. This study used the descriptive qualitative method. The goal is to understand the existence of legal protection for consumers, especially those affected by online loans. The result is that laws and regulations are governing online loans. It also includes consumer protection. The government has taken firm steps in collaboration with OJK and Kominfo to eradicate illegal fintech crimes. This is to protect the public and grow the public regarding financial education.